Lowering the dielectric constant of polyimide thin films by swelling with supercritical carbon dioxide. (18th March 2013) - Ronova, Inga A.; Bruma, Maria; Kuznetsov, Alexander A.; Nikolaev, Alexander Yu.
Abstract : The swelling with supercritical carbon dioxide (sc‐CO2 ) of thin films of polyimides having various structures was investigated. It was shown that the degree of swelling is significantly influenced by the solvent which was used for the synthesis of those polyimides, by the solvent which was used for the preparation of thin films and by the conformational rigidity of the polymers. The presence of hexafluoroisopropylidene groups in the main chain of a polymer prevents its swelling with sc‐CO2 . The best results were obtained for polyimide film ULTEM, based on m‐phenylene‐diamine and isopropylidene‐diphenoxy‐bis(phthalic anhydride), synthesized in benzoic acid, whose free volume increased twice and its dielectric constant decreased from 3.15 to 2.45 by swelling with sc‐CO2 . Copyright © 2013 John Wiley & Sons, Ltd.